Macrophage migration inhibitory factor contributes to ethanol-induced liver injury by mediating cell injury, steatohepatitis and steatosis - Barnes, Mark A. (2013)
MIF, a multi-potent protein that exhibits both cytokine and chemotactic properties, is expressed by many cell types, including hepatocytes and non-parenchymal cells. We hypothesized that MIF is a key contributor to liver injury after ethanol exposure. Female C57BL/6 or MIF−/− mice were fed an ethanol-containing liquid diet or pair-fed control diet for 4 (11% total kcal; early response) or 25 (32% kcal; chronic response) days. Expression of MIF mRNA was induced at both 4d and 25d of ethanol feeding. After chronic ethanol, hepatic triglycerides and plasma ALT and AST were increased in wild-type, but not MIF−/−, mice. In order to understand the role of MIF in chronic ethanol-induced liver injury, we investigated the early response of wild-type and MIF−/− to ethanol. Ethanol feeding for 4d increased apoptosis of hepatic macrophages and activated complement in both wild-type and MIF−/− mice. However, TNFα expression was increased only in wild-type mice. This attenuation of TNF-α expression was associated with fewer F4/80+ macrophages in liver of MIF−/− mice. After 25d of ethanol feeding, chemokine expression was increased in wild-type mice, but not MIF−/− mice. Again, this protection was associated with decreased F4/80+ cells in MIF−/− mice after ethanol feeding. Chronic ethanol feeding also sensitized wild-type, but not MIF−/−, mice to lipopolysaccharide, increasing chemokine expression and monocyte recruitment into the liver. CONCLUSION: Taken together, these data indicate that MIF is an important mediator in the regulation of chemokine production and immune cell infiltration in the liver during ethanol feeding and promotes ethanol-induced steatosis and hepatocyte damage.